Prosedur Pemeriksaan MSCT Pelvis Studi Kasus Tumor Pelvis di Instalasi Radiologi RSUD Muhammad Sani Karimun - Wedayanti, Luh Deva; Juliasa, I Wayan; Suci, Puspa Pamella (Poltekkes Kemenkes Semarang, 2026)
Background: Multislice Computed Tomography (MSCT) is widely used for pelvic imaging because of its high spatial resolution, rapid acquisition time, and multiplanar reconstruction capability. Pelvic tumors require detailed evaluation of their margins, extent, and anatomical relationships with surrounding structures. At Muhammad Sani Hospital Karimun, MSCT pelvis examinations for suspected pelvic tumors are performed using a two-stage protocol: an initial intravenous (IV) contrast-enhanced scan followed by a second scan utilizing intragenital iodine contrast and rectal air as negative contrast. This imaging approach differs from standard MSCT pelvis protocols and is applied to improve visualization of tumor boundaries in selected cases. Methods: This study is a descriptive observational study in the form of a case report involving a single patient who underwent a two-stage MSCT pelvis examination. Result: The first stage, using IV contrast enhancement, provided information regarding tumor location, density characteristics, and possible extension but was limited in clearly defining tumor margins. The second stage involved intragenital administration of iodine contrast through catheterization and rectal air insufflation, which improved visualization of the anatomical boundaries between the tumor, urinary bladder, and rectosigmoid colon. Imaging findings were assessed descriptively without inferential statistical comparison between techniques. A cystic-solid mass measuring 10.5 × 6.2 × 8.4 cm was identified in the right pelvic region, along with an isodense mass measuring 4.0 × 6.2 cm in the left pelvis. The combined imaging approach subjectively enhanced visualization of tumor margins and anatomical relationships compared to the initial IV contrast scan alone, thereby increasing diagnostic confidence in tumor characterization. Conclusions: The two-stage MSCT pelvis protocol using IV contrast followed by intragenital iodine contrast and rectal air may provide improved visual delineation of pelvic tumor margins in this observed case. This technique represents a practical clinical variation of the anal marker method. However, the observed improvement is descriptive in nature and not based on comparative inferential analysis. Further studies with larger sample sizes and standardized comparison are required before drawing definitive conclusions or recommending routine implementation of this protocol.